Proceedings Electronic Components and Technology, 2005. ECTC '05.
DOI: 10.1109/ectc.2005.1441388
|View full text |Cite
|
Sign up to set email alerts
|

Pb-free Assembly, Rework, and Reliability Analysis of IPC Class 2 Assemblies

Abstract: A team of NEMI companies collaborated for three years to develop Pb-free assembly and rework processes for doublesided, 14-layer, printed circuit boards (PCB) in two thicknesses (0.093" and 0.135") with electrolytic NiAu and Immersion Ag surface finishes. This work followed the initial SMT manufacturing feasibility effort carried out by the first NEMI Pb-free development team (1999)(2000)(2001)(2002). All SMT assembly, PTH wave assembly and component rework processes were carried out on production equipment. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This visual surface appearance cannot be used to definitively identify solder as being lead bearing or lead-free, nor should it be used as an indicator of reliability or lack there of. It has been reported that reflow in nitrogen can improve the visual appearance of the surface of the lead-free solder joints but have no positive impact on reliability (Gleason et al, 2005).…”
Section: Analysis Methods Results and Discussionmentioning
confidence: 99%
“…This visual surface appearance cannot be used to definitively identify solder as being lead bearing or lead-free, nor should it be used as an indicator of reliability or lack there of. It has been reported that reflow in nitrogen can improve the visual appearance of the surface of the lead-free solder joints but have no positive impact on reliability (Gleason et al, 2005).…”
Section: Analysis Methods Results and Discussionmentioning
confidence: 99%